1991
DOI: 10.1161/01.str.22.10.1303
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of low cerebral intracellular pH in rats during hyperbaric hypercapnia.

Abstract: Background and Purpose: Brain addosis from cerebral ischemia is characterized by average intraceiiular pH levels of approximately 5.8-6.2, which appear in turn to worsen cellular injury. We report that the brain is not injured when hypercapnia is used to reduce intraceiiular pH to about 62 during adequate oxygenation. A hyperbaric chamber is needed to achieve intraceiiular pH values so low because inspired CO 2 tensions must be increased to approximately 1 atm.Summary of Report: Using in vivo phosphorus-31 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 18 publications
2
10
0
3
Order By: Relevance
“…This was slightly lower than the average minimum pHi value ( 4 . 3 ) tolerated by the cardiovascular system of the entire group of rats (3). We also note that when the oxygen tension in the chamber was 1 ATA, a shift of -0.2 ppm towards higher resonance frequencies was seen for all peaks in the spectra, consistent with a small bulk magnetic susceptibility shift from paramagnetic oxygen.…”
Section: Physiological Monitoringsupporting
confidence: 61%
See 1 more Smart Citation
“…This was slightly lower than the average minimum pHi value ( 4 . 3 ) tolerated by the cardiovascular system of the entire group of rats (3). We also note that when the oxygen tension in the chamber was 1 ATA, a shift of -0.2 ppm towards higher resonance frequencies was seen for all peaks in the spectra, consistent with a small bulk magnetic susceptibility shift from paramagnetic oxygen.…”
Section: Physiological Monitoringsupporting
confidence: 61%
“…A schematic diagram o f t h e "T"-piece arrangement and pneumatically controlled valve i s given in Fig 3 is the chamber pressure.) During tests of the system, a balloon was fixed to the location going "to the animal," where the endotracheal tube would normally be.…”
Section: Gas Manifolds Circuits and Special Valvementioning
confidence: 99%
“…Indeed, although application of the Henderson-Hasselbach equation with a cytosolic HC0 3 -concentration of 10mM/L (19) predicts pHi values of 6.62 and 6.32 for Pco, of respectively 100 and 200 mm Hg, studies of hypercapnia up to 200 mm Hg consistently reported pHi above 6.80 (21,25,26,29), with one exception (29). To our knowledge, the lowest pHi ever reported in normoxic hypercapnia is the value of 6.2 measured by Xu and colleagues (30) in the rat brain exposed to a Pco 2 of 750 mm Hg in hyperbaric conditions. Thus, due in large part to powerful regulatory mechanisms, normoxic hypercapnia has a limited potential for creating severe intracellular acidosis.…”
Section: Effects Of Hypercapnia On the Cellmentioning
confidence: 96%
“…Dennoch kommt es zu Veränderungen, die die Funktion bestimmter Organsysteme wesentlich beeinflussen können. So verursacht der Anstieg des PaCO 2 eine Reduktion der Aktivität kontraktiler Zellelemente [16] und führt zu einer Umstellung der Energiegewinnung, ohne daß es aber zu einer Abnahme des intrazellulären ATP-Gehalts kommt [23]. Die zelluläre Sauerstoffaufnahme ist durch die pH-bedingte Rechtsverschiebung der Sauerstoffbindungskurve unter Hyperkapnie erleichtert, ohne notwendigerweise zu einer Einschränkung der pulmonalen Sauerstoffaufnahme zu führen.…”
Section: Wirkung An Der Zelleunclassified